Pola Gerusan Lokal Pada Model Pilar Jembatan Lingkaran Ganda (Double Circular) - M Tony Iskandar; Mudjiatko Mudjiatko; Trimaijon Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Pillar of the bridge on the stream causes changes flow patterns and local scour. Local scour will decrease the power of pillar to sustaining bridge load. Laboratory model was conducted to determine the model of local scour phenomena double circular pillar with or without protector curtain type. Basic canal model is using kampar sand with grain size d35 = 0,285 mm, d50 = 0,330 mm and d65 = 0,380 mm and spesific weight is 2,64.Froude number that used is Fr1=0,464, Fr2=0,670 and Fr3=0,769. Reynold number Fr1 scored 1658,42 is classified as transitional flow, Fr2 scored 3081,68 and Fr3 scored 4381,19 is classified as turbulent flow. Shield shows the use of gradation in moving zone. Hydrodynamic flow in pillar causes down flow that showed by scour in upstream pillar. Scour rech the equilibrium stage at minute 75. The ratio of scour depth ds/b is range from 0,03 – 0,46. The use of swivel can reduce the scours depth until 44,44%. Sediment transport analysis prove that the higher Froude is used the bigger the granules are transported. Key word : scour, model laboratory, double circular, froude, reynold, Shields, hydrodynamic flow, sediment transport .